MANAJEMEN STRATEGI MENINGKATKAN JUMLAH PENGUNJUNG MUSEUM KERIS NUSANTARA SURAKARTA PADA MASA PANDEMI - Darmaesti (Lembaga Pengembangan Kinerja Dosen, 2022)
This paper has a purpose to provide an understanding at the importance of museums as tourist attractions and places of learning or fun educational facilities and to find out the management strategies implemented by the Keris Nusantara Surakarta museum to increase visitors pandemic era. This research used qualitatif methodology by applying a qualitatif approach to the description of several relevant articles in collecting data and information and adjusting the problems taken, namely the data obtained based on site observations, literature review and document review. By visiting the Keris Nusantara Surakarta museum, it is hoped that a sense of nationalism will grow in visitors to be proud and love the homeland. The results showed that people’s interest to visit the museum in pandemic era is still low, so the management of the Keris Nusantara Surakarta museum must carry out several strategies to increase the number of visitors. The strategies that have been carried out are making public programs, changing the collection of kris so that visitors don't get bored with the collections on display, placing the keris donated by President Jokowi as an icon and attraction, equipping the museum with comfortable facilities for visitors, maintaining security and cleanliness of the museum area, preparing trained human resources.